(untitled) (International journal of medical sciences, 2025)
Asphyxial deaths represent an important category in forensic pathology, involving various mechanisms that lead to reduced oxygen exchange and cellular hypoxia. Recognizing the morphological and histopathological alterations linked to asphyxia is crucial for proper death certification, distinguishing it from other sudden death causes, and uncovering underlying mechanisms like strangulation, smothering, positional asphyxia, and drowning. This review provides an overview of the existing knowledge regarding the macroscopic, microscopic, and additional findings typical of asphyxial deaths.